ENTROPY METHODS IN ANALYSIS OF BIOLOGICAL SYSTEMS - O. G. Berestneva; Ya. S. Pekker; S. S. Murzina (Бюллетень сибирской медицины)
The adaptation of people to new production environment are often influenced by very unusual, excessive and harsh environmental factors, genetically inadequate to its nature. Human adaptation to the new production conditions can be summarized as a set of social and biological properties and characteristics needed to sustain the existence of the human body in a particular ecological environment.It is necessary under the new conditions to achieve harmony of human interaction with the physical environment of their lives, adequate human nature. In addressing this fundamental problem of the primary role belongs to biomedical science, which should not so much to predict the appearance of the disease, how much help to preserve and improve the health of population. At the same time becoming increasingly clear that solving this problem adaptation theory plays a crucial role.Adaptive features appear only in real life. It is in particular natural or artificial habitat capabilities of the body, when the survival and life require maximum mobilization and stress its potential adaptive capacity. Consequently, the property adaptation of living systems is, in fact, a measure of individual health.An approach based on entropy methods for modeling complex systems, seems to be the most promising for integrated assessment of biological systems.